Fostering accessible tourism: stakeholders’ perspective in Vila do Conde and Póvoa de Varzim - Liberato, Dália (2022)
Nowadays, tourism is considered an important social phenomenon, stimulating the mobility of millions of tourists around the world. Accessible tourism is becoming increasingly visible and is considered a growing market segment. For this, it is essential to adapt infrastructures, making them fully accessible. This research seeks to raise awareness in the tourism sector for the creation of accessibility conditions necessary and aimed at all types of demand. In this way, it is intended to deepen the knowledge about Accessible Tourism, as well as evaluate, on the supply side, the awareness and consciousness of the importance of this segment and ascertain whether Vila do Conde and Póvoa de Varzim, meet all the necessary conditions to receive these tourists. This study adopts a qualitative approach with the application of interviews to seven entities, representative of the supply in the destinations, dealing daily with mobility impaired people. The main results show that, despite Accessible Tourism being an increasingly important market segment for the tourism industry, the existing tourism offer in the cities of Vila do Conde and Póvoa de Varzim (North of Portugal), is not yet fully aware and adapted to receive and serve people with reduced mobility.